Mixed methods evaluation of the Getting it Right First Time programme - improvements to NHS orthopaedic care in England: study protocol. Issue 1 (December 2017) - Barratt, Helen; Turner, Simon; Hutchings, Andrew; Pizzo, Elena; Hudson, Emma; Briggs, Tim; Hurd, Rob; Day, Jamie; Yates, Rachel; Gikas, Panagiotis; Morris, Stephen; Fulop, Naomi; et al.
Abstract Background Orthopaedic procedures, such as total hip replacement and total knee replacement, are among the commonest surgical procedures in England. The Getting it Right First Time project (GIRFT) aims to deliver improvements in quality and reductions in the cost of NHS orthopaedic care across the country. We will examine whether the planned changes have delivered improvements in the quality of care and patient outcomes. We will also study the processes involved in developing and implementing changes to care, and professional and organisational factors influencing these processes. In doing so, we will identify lessons to guide future improvement work in other services. Methods/design We will evaluate the implementation of the GIRFT programme, and its impact on outcomes and cost, using a mixed methods design. Qualitative methods will be used to understand the programme theory underlying the approach and study the effect of the intervention on practice, using a case study approach. This will include an analysis of the central GIRFT programme and local provider responses. Data will be collected via semi-structured interviews, non-participant observation, and documentary analysis. Quantitative methods will be used to examine 'what works and at what cost?' We will also conduct focus groups with patients and members of the public to explore their perceptions of the GIRFT programme. The research will draw on theories of adoption, diffusion, and sustainability of innovation; its characteristics; and contextual factors at provider-level that influence implementation. Discussion We will identify generalisable lessons to inform the organisation and delivery of future improvement programmes, to optimise their implementation and impact, both within the UK and internationally. Potential challenges involved in conducting the evaluation include the phased implementation of the intervention in different provider organisations; the inclusion of both retrospective and prospective components; and the effects of ongoing organisational turbulence in the English NHS. However, these issues reflect the realities of service change and its evaluation.